Policy Instruments to Support Agroecological Transitions in Europe. (9th December 2022) - Gava, Oriana; Povellato, Andrea; Galioto, Francesco; Pražan, Jaroslav; Schwarz, Gerald; Quero, Alba Linares; Iragui, Uxue Yoldi; Massa, Carlos Astrain; Zīlāns, Andis; Carolus, Johannes
Summary: Agroecological transitions have the potential to deliver multiple environmental and social benefits. However socio‐economic barriers have prevented those transitions in many European contexts. This article aims to inform policymakers about policy instruments that can foster agroecological transitions in Europe, especially by removing key socio‐economic barriers. A multi‐step methodology was carried out over a two‐year period in 15 case studies across Europe. The case studies represent farming systems that are in the process of initiating or enhancing the transition. Data collection relied on a participatory process, involving a variety of transdisciplinary actors. Study findings identify three major themes of barriers to agroecological transitions, namely actor capacity, value chain and policy . To address these barriers, policy instruments should consider the farming system's stage in the transition pathway to take account of the different priorities of local actors. At the stage of initiating the transition, removing the barriers requires improvements in knowledge delivery mechanisms by strengthening advisory services and reducing decision‐makers' uncertainty. At the stage of enhancing the transition, a focus on social capital is needed, for example by strengthening networking and cooperation measures. Generally, more attention towards state interventions which support the transitions to agroecology is needed, such as developing new voluntary agroecology certification schemes and public procurement initiatives. Des instruments de politique pour accompagner les transitions agroécologiques en Europe: Les transitions agroécologiques pourraient apporter de multiples avantages environnementaux et sociaux. Des barrières socio‐économiques ont pourtant empêché ces transitions dans de nombreux contextes européens. Cet article vise à informer les décideurs sur les instruments d'action publique susceptible de favoriser les transitions agroécologiques en Europe, notamment en supprimant les principales barrières socio‐économiques. Une méthodologie en plusieurs étapes a été appliquée sur une période de deux ans dans 15 études de cas à travers l'Europe. Ces études de cas représentent des systèmes agricoles qui sont en train d'amorcer ou d'améliorer leur transition. La collecte de données s'est appuyée sur un processus participatif impliquant une variété d'acteurs transdisciplinaires. Les résultats de l'étude identifient trois grandes catégories d'obstacles aux transitions agroécologiques, à savoir la capacité des acteurs, la chaîne de valeur et l'intervention publique. Pour surmonter ces obstacles, les instruments d'action doivent tenir compte de l'étape vers la transition du système agricole afin de tenir compte des différentes priorités des acteurs locaux. Au stade du lancement de la transition, la suppression des obstacles nécessite des améliorations dans les mécanismes de diffusion des connaissances en renforçant les services de conseil et en réduisant l'incertitude des décideurs. Au stade de l'amélioration de la transition, il est nécessaire de mettre l'accent sur le capital social, par exemple en renforçant les mesures de mise en réseau et de coopération. En règle générale, il faut porter une plus grande attention aux interventions de l'État qui soutiennent les transitions vers l'agroécologie, telles que le développement de nouveaux programmes volontaires de certification agroécologique et des initiatives en matière de marchés publics. Politische Instrumente zur Unterstützung des agrarökologischen Wandels in Europa: Der agrarökologische Wandel hat das Potenzial, vielfältige ökologische und soziale Vorteile zu bringen. Allerdings haben sozioökonomische Barrieren diese Umstellung in vielen europäischen Zusammenhängen verhindert. Ziel dieses Artikels ist es, politische Entscheidungsträger über politische Instrumente zu informieren, die den agrarökologischen Wandel in Europa fördern können, insbesondere durch die Beseitigung zentraler sozioökonomischer Hindernisse. Eine mehrstufige Methodik wurde über einen Zeitraum von zwei Jahren in 15 Fallstudien in ganz Europa angewandt. Bei den Fallstudien handelt es sich um landwirtschaftliche Systeme, die sich in der Phase der Umstellung befinden oder diese vorantreiben. Die Datenerhebung stützte sich auf einen partizipativen Prozess, an dem eine Vielzahl von transdisziplinären Akteuren beteiligt war. Die Ergebnisse der Studie zeigen drei Hauptthemen von Hindernissen für agrarökologische Umstellungen auf, nämlich die Kapazitäten der Akteure, die Wertschöpfungskette und die Politik. Um diese Hindernisse zu beseitigen, sollten die politischen Instrumente das Stadium des landwirtschaftlichen Systems auf dem Übergangspfad berücksichtigen, sodass den unterschiedlichen Prioritäten der lokalen Akteure Rechnung getragen wird. In der Einleitungsphase des Übergangs erfordert die Beseitigung der Barrieren eine Verbesserung der Mechanismen zur Wissensvermittlung, indem die Beratungsdienste gestärkt und die Unsicherheit der Entscheidungsträger verringert werden. In der Phase der Festigung des Übergangs muss der Schwerpunkt auf das soziale Kapital gelegt werden, beispielsweise durch die Stärkung von Netzwerken und Kooperationsmaßnahmen. Generell ist mehr Aufmerksamkeit für die staatlichen Interventionen erforderlich die den Übergang zur Agrarökologie unterstützen, wie z.B. die Entwicklung neuer freiwilliger agrarökologischer Zertifizierungssysteme und öffentlicher Beschaffungsinitiativen.